Longterm melatonin administration alleviates paraquat mediated oxidative stress in Drosophila melanogaster.
We investigated the effect of melatonin (MEL) in the activities of cytosolic superoxide dismutase (SOD) and catalase as well as in the levels of H2O2 and mitochondrial malondialdehyde (MDA) in paraquat-intoxicated Drosophila melanogaster. Paraquat (40 mM) was administrated for 36 h. Three groups of flies intoxicated with paraquat were used: PQ (exposed during 36h to paraquat), PQ-MEL (exposed during 36h to paraquat and then treated with MEL [0.43 mM] for 12 days) and PQ-Control (maintained in standard corn meal for 12 days). Two additional groups without pre-intoxication with PQ were added: Control (maintained in standard corn meal) and MEL (treated with MEL for 12 days). Immediately after PQ intoxication the concentration of MDA (17.240 Â